Efeito de vacinas alopática e homeopática frente a Mycobacterium spp em diferentes modelos animais - Cavalcanti, Marcos Antônio Rocha (2013)
The development of new vaccines in the control of various diseases in cattle has been increasing the marketing of animals and animal products. Thus we tested two vaccines, a biotherapy homeopathicvaccine and other recombinantallopathic vaccine,using mycobacteria in their formulations that were subsequently tested in mice and cattle. In order to study the prophylactic effect of homeopathic vaccine and the potency to be used as a vaccine, we used a model of immunizations and infections. To this end, we used mice female of BALB / c lineage which were distributed in 15 groups of three animals each. To assess the possible immune mechanisms involved in homeopathic biotherapy vaccinations we used Mycobacterium massiliense. The biotherapics were prepared from mycobacterial M. massiliense. After infections and immunizations, the animals were euthanized and their livers and spleens were harvested, macerated, homogenized, plated and incubated at 37 ° C for five days. Then we did the counting of colony forming units (CFU) of bacteria recovered from organs and according to the results obtained were selected the potencies11cH and 19cH to be tested as vaccine, because they have shown more homogeneous results. In the animals that were immunized with 19 cHthere were induction of IgG2a class antibodies specific to M. massiliense similar to (0.18 ± 0.07) infections alone (0.19 ± .02). To assess allopathic vaccine protection was used mycobacterium (Mycobacterium smegmatis mc2155 with PLA71/Fusion) in cattle. After allopathic vaccinations, blood was collected and serum was removed for ELISA test. Animals that received the recombinant live vaccine expressing protein of fusion showed greater levels of specific antibodies (p <0.01). This study evaluated the effect ofhomeopathic biotherapy vaccine composed of M. massiliense and allopathicvaccine formulated with M.smegmatis recombinant in different animal models, thus concluding that both vaccines and vaccines homeopathic and allopathic using different kinds of mycobacteria can induce humoral immune response in an animal model.